Analisis Sensitivitas Fungsi Tujuan terhadap Biaya Pemupukan Tanaman Durian Oranye Berdasarkan Fase Pertumbuhan Tanaman - Lutfi Shofiya (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine a mathematical model for optimizing durian tree fertilization costs based on growth phases, to identify the optimal fertilization cost solution for each growth phase using this model, and to analyze the sensitivity of the objective function for durian tree fertilization costs. The objective function in this study is to minimize total fertilization costs at each growth phase while considering the constraints of the plant’s nutrient requirements. The research stages were conducted through a mathematical modeling process comprising Understanding, Simplifying, Mathematizing, Working Mathematically, Interpreting, Validating, and Exposing. The optimal solution was obtained using the simplex method with the assistance of POM-QM software version 5.2. Subsequently, a sensitivity analysis was performed to assess the stability of the optimal solution to changes in the coefficients of the objective function. The results of the study indicate that the optimal solution remains stable as long as changes remain within the lower bound and upper bound, ensuring that fertilization decisions for each growth phase can still be implemented optimally.
Approved by Teddy
Keywords: Analisis Sensitivitas; optimasi; biaya pemupukan; tanaman durian